Studies of Mhd Flow on Stretching Surface Through Porous Medium With Heat Transfer: Impact of Magnetic Field and Porosity on MHD Flow and Heat Transfer (Journal of Advances and Scholarly Researches in Allied Education, 2011)
This Paper analyzed the effectson magnetic field of an incompressible viscous fluid past a porous plate i.e.the fluid is electrically conducting, the effects of the porosity of themedium, the surface stretching velocity, The heat generation coefficient onboth the flow and heat transfer are presented. A numerical solution for thegoverning nonlinear momentum and energy equations is obtained.